PEMANFAATAN TANAMAN OBAT KELUARGA MELALUI PROGRAM ASMANTOGA UNTUK MENDUKUNG UPAYA KESEHATAN TRADISIONAL DESA TAROKAN PROBOLINGGO: penelitian kualitatif deskriptif - Muhammad Faiq Nashrullah; Rahma Dea Agustin; Wan Nurhayati; Fakhrizal Anas; Risma Nabila Mandasari; Eliza Laila Ardhani; Alfina Lailatul Karima; Mohammad Nabil Ihsan; Laila Uswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Family Medicinal Garden Self-Care Program (Asmantoga) is a community empowerment initiative aimed at promoting the use of medicinal plants to strengthen traditional health practices. This program was implemented in Tarokan Village, Banyuanyar District, Probolinggo Regency, with the goal of increasing community awareness and skills in cultivating and processing medicinal plants. A qualitative approach using the Participatory Action Research (PAR) model was employed, involving active participation from local residents throughout all stages of the program. The activities included seminars and public awareness sessions, planting and decoration competitions, and hands-on training in herbal product processing. The results showed improved community knowledge and skills in utilizing medicinal plants, the establishment of household TOGA gardens, and greater independence in maintaining family health using natural methods. Additionally, the program strengthened social solidarity and the preservation of local wisdom in traditional medicine.